A STUDY ON THE ABILITY OF THE THIRD SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU IN PRONOUNCING PURE VOWEL SOUNDS - Mira Wahyu Anggrain; Fadly Azhar; Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This decriptive research is aim to find out the ability of the third semester students of English Study Program FKIP Universitas Riau in pronouncing pure vowel sounds. The sample of this research is one of the three class of the third semester studentsof English Study Program which are chosoe by using cluster sampling technique. The number of sample is 36 students. The data were collected by giving a pronunciation test to the student individually. The test asked the students to read a text and the researcher record it. The students’ score were analyzed by using Harris’ scoring system which concerned with eleven sounds of English pure vowel, they are vowel /iː/, vowel /ɪ/, vowel /ʊ/, vowel /uː/, vowel /e/, vowel /ə/, vowel /ɜː/, vowel /ɔː/, vowel /æ/, vowel /ʌ/, and vowel /ɑː/ The findings show that the students’ mean score for each sounds of English pure vowel was in “good” level where the students’ ability in terms pronouncing vowel /ɪ/ was the highest among the other aspects with the mean score 91, while pronouncing vowel /ə/ was the lowest one, with the mean score 67. Based on the results obtained, it can be inferred that the students are able to pronounce pure vowel sounds and their level of ability is in “good” level with the mean score 77. By lookng to the aspect the students mostly weak, that is pronouncing vowel /ə/, this study recommended the students to more practice in pronouncing vowel /ə/ to improve their ability in pronunciation.Key Words: Study, Ability, Pronunciation, Pure Vowel